THE FILIPINO WOMAN: A Gendered History - J. Aguja, Hilton (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper explores the historical, religious and philosophical underpinnings of how women have been relegated into the background in recent years by tracing the history of women in the Philippines. The respected status Filipino women enjoyed during the pre-Spanish Philippines were predicated on the notion of equality and partnership dictated by the social roles played by both men and women. Spanish conquest of the Philippines altered the hitherto existing social order. The Spanish imposed religion in the colony which had so much misogynistic ideas that demeaned women. Centuries of Spanish colonialism had disfigured the social landscape for women in the Philippines. Womanhood was bestowed with new meanings to the disadvantage of women. And yet the women of the Philippines themselves had been vindicated and they have restored the social status of respect they once enjoyed. Currently, the entire legal system of the Philippines had already taken cognizance of the important role of women in nation building. What remains is whether or not such policy pronouncements get implemented.